Analisis Preferensi Mahasiswa Terhadap Platform E-Commerce di Era Digital - Rido Galih Alief; Muhammad Sakir Haruna (Pantarei, 2026)
This study aims to analyze the preferences of students of the State Polytechnic of Creative Media towards e-commerce platforms using the Simple Additive Weighting (SAW) method. The background of the study is based on the rapid development of e-commerce in Indonesia, followed by increasing student participation as active users. This study uses a quantitative approach with a Likert-scale questionnaire instrument that measures five main criteria, namely price, ease of use, service quality, delivery speed, and promotion. The data obtained are then processed using the SAW method to determine the ranking of e-commerce platforms based on preference scores. The results show that promotion and price factors are the most dominant criteria in influencing student preferences, followed by ease of use, service quality, and delivery speed. Based on the results of the SAW method calculation, the Shopee platform is ranked first as the platform that best suits student preferences, followed by Tokopedia and Lazada. These findings indicate that students tend to choose platforms that offer economic benefits as well as a good user experience. This study contributes to the development of multi-criteria decision-making methods in the context of digital consumer behavior. In addition, the results of this study can also be a reference for e-commerce industry players in designing more effective marketing strategies that are oriented towards user needs, especially students. Thus, this research has not only academic relevance but also practical implications for developing a competitive and sustainable e-commerce ecosystem.